Virus "X" y virus "Y" en cultivos de papa de Mendoza - Pontis, Rafael E. (1962)
Potato virus X abd Y on potato crops in Mendoza. The presence of potato viruses X (solanum virus 1 SMITH; Annulus dubius HOLMES) and Y (Solanum virus 2 SMITH; Marmor upsilon HOLMES) on potato crops (Solanum tuberosum L. var. White Rose and var. Up-to-Date) is determined. The virus Y had not been reported up to the present in any host in Mendoza, while the virus X was reported on tomato (Lycopersicon esculentum MILL.), and, exclusively on sintomatological observations bases, on potato crops. The methods followed are described and the results are analized.